Biomass yield and chemical composition of the cassava plant over two vegetative growth cycles - Menegucci, Nathane Colombo [UNESP]; Leonel, Magali [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Nunes, Jesion Geibel da Silva [UNESP]; Nunes, Jason Geter da Silva [UNESP] (Universidade Estadual de Maringa, 2024)
The objective of this work was to study the biomass production and chemical composition of the different parts of the cassava plant during the first and second vegetative cycles, with the aim of providing data that can contribute to the understanding of the response of cassava cultivars to different harvest ages. The experimental design consisted of randomized blocks in split plot scheme. Plots were represented by cultivars IAC 90 and IAC 118-95 and subplots by crop age (2, 4, 6, 8, 10, 12, 14, 16, and 18 months after planting). Our results showed that the ‘IAC 90’ allocated a higher proportion of assimilates to the leaves, stem and planted cutting than the ‘IAC 118-95’, which was more efficient in allocating dry matter to the storage roots. Storage roots showed an increase of more than 50% in starch content 14 months after planting. The cultivar IAC 118-95 is distinguished by the higher harvest index, allowing earlier harvesting, with possible valorisation of the leaves as industrial raw material. Variables showed different degrees of inter-relationships amongst themselves. Total plant fresh matter and dry matter yields were positively correlated with growth parameters and root starch for both cultivars. Harvest time and cultivar are key factors that should be considered to increase profits in the cassava agro-industrial chain.
Keywords: crop age; cultivar; dry matter allocation; harvest index